Bispens sidste hvilested? Middelalderlige bispers seglstamper fundet på kirkegårde - Andersen, Michael (Hikuin, 2000)
The bishop’s last resting-place? Medieval bishops’ seal matrices found in cemeteries By Michael Andersen When a medieval seal matrix is found in a cemetery or under the floor of a church the conclusion will usually be that the owner of the matrix was buried in this specific burial ground. It was common to bury a person together with his seal matrix, broken or intact. A group of five bishops’ seal matrices found in Danish, Norwegian and Swedish cemeteries form an exception, however. It is remarkable that none of them was found within the diocese of the bishop in question. Most of them were actually found outside the country, where the bishop functioned. Furthermore it is strange that all the matrices are made of lead, a poor material for a bishop’s seal. The matrices cannot be regarded as proper seals, and it is not reasonable to see these finds as indications of bishops’ graves. For what purposes were these matrices made? A number of solutions are discussed in brief. They could be trial pieces, seals to send along with the bishop’s substitute, seals for exchange with partners abroad so they could know the correct seal for correspondence, sigilla citationis, fakes, special seals for letters of indulgence, burial seals. It is not the aim here to reach a final solution, only to indicate that these seals were made for a special purpose different from the conventual sealing of deeds. Why are they found in churchyards? It is suggested that they after fulfilling their original purposes were used as amulets. A seal matrix with the picture of a bishop could be a fine amulet, and it is reasonable to believe that they were placed in graves as religious amulets.